Difficult phylogenetic questions: more data, maybe; better methods, certainly - Philippe, Hervé (BioMed Central, 2011)
Contradicting the prejudice that endosymbiosis is a rare phenomenon, Husník and co-workers show in BMC Biology that bacterial endosymbiosis has occured several times independently during insect evolution. Rigorous phylogenetic analyses, in particular using complex models of sequence evolution and an original site removal procedure, allow this conclusion to be established after eschewing inference artefacts that usually plague the positioning of highly divergent endosymbiont genomic sequences. See research article http://www.biomedcentral.com/1741-7007/9/87